2018
DOI: 10.1111/jgh.14302
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of post‐endoscopic submucosal dissection electrocoagulation syndrome for colorectal neoplasm

Abstract: This study identified the risk factors for PECS. Patients with high-risk factors of PECS require careful management after colorectal ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 26 publications
0
49
2
5
Order By: Relevance
“…Consequently, it is essential to know whether cases have risk factors for PECS when endoscopists perform colorectal ESD. Several studies have shown that female patients, tumor location, a long procedure time, submucosal fibrosis, and larger tumor size are risk factors for PECS 5,14,16,36,44 . Although other risk factors are still controversial, the lesion in the right side of the colon have been revealed as an important potential risk factor for PECS in many studies 15,34,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is essential to know whether cases have risk factors for PECS when endoscopists perform colorectal ESD. Several studies have shown that female patients, tumor location, a long procedure time, submucosal fibrosis, and larger tumor size are risk factors for PECS 5,14,16,36,44 . Although other risk factors are still controversial, the lesion in the right side of the colon have been revealed as an important potential risk factor for PECS in many studies 15,34,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The rates of delayed bleeding, delayed perforation, and PECS after colorectal ESD are reported to be 1.5–11.9%, 0.3–0.7%, and 4.8–40.8%, respectively, in previous studies 6–16 . To reduce the risk of AEs, several studies have suggested prophylactic endoscopic closure of the mucosal defect after colorectal ESD 17–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation syndrome (CS) is transmural burn syndrome resulting from electrocoagulation injury in the bowel wall after endoscopic treatments including polypectomy, EMR and ESD [22,33,34]. CS is clinically diagnosed based on the presence of abdominal tenderness and/or rebound tenderness matched procedure site by transmural burn and localized peritonitis resulting to serosal inflammation, fever, leukocytosis, and elevated C-reactive protein levels without obvious perforation on abdominal radiography and/or CT scan after endoscopic treatment [22,33,34].…”
Section: Post-esd Coagulation Syndromementioning
confidence: 99%
“…The previously known risk factors of post-ESD CS are sex, tumor size, procedure time, tumor location and presence of submucosal fibrosis [22,33,34,36,37]. Right side colon is a known risk factor of post-ESD CS, and the cecum is a part that is a higher risk for adverse events related endoscopic procedures, including post-ESD CS than other parts of the colon [22,34,38]. It is supposed that the cecal wall is thinner than the other parts of colon and air insufflation during the procedure generates a higher pressure in the cecum than in other parts of the colon, thereby increasing vulnerability to injury [22,38].…”
Section: Post-esd Coagulation Syndromementioning
confidence: 99%
See 1 more Smart Citation